Analisis Evaluasi Kualitas Air pada Proses Instalasi Pengolahan Air Limbah (IPAL) di Salah Satu Rumah Sakit Wilayah Surabaya Barat - Islami, Aquila Nuh; Mirwan, Mohammad (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Hospital wastewater has characteristics that distinguish it from wastewater generated by other human activities. The purpose of this study is to analyze and evaluate the operation of Hospital Wastewater Treatment Plants in West Surabaya and assess how well they affect the quality of the wastewater they produce. The research method applied is direct observation of the WWTP process and discussion with the person in charge of the hospital's WWTP in West Surabaya. The evaluation results show that some WWTP process units are operating according to standards, but some process sections show a decrease in efficiency, which impacts the quality of the water produced. The average removal rate for the parameters BOD5 was 95.03%, COD was 93.73%, NH3-N was 99.9%, and PO4 was 96%. These results indicate that all parameters meet the applicable quality standards and optimization of the maintenance of the WWTP system is required.